Solid state polymerization of pet/pc extruded blend: effect of reaction temperature on thermal, morphological and viscosity properties - Mendes,Luis Claudio (2014)
A systematic study of solid state polymerization (SSP), concerning the melt extruded blend of poly(ethylene terephthalate)/polycarbonate (catalyzed PET/PC, 80/20 wt %), as a function of temperature range (180-190°C) for a fixed time (6 h) is presented. The materials obtained were evaluated by differential scanning calorimetry (DSC), thermogravimetry/derivative thermogravimetry (TG/DTG), optical microscopy (OM) and intrinsic viscosity (IV) analysis. After SSP, at all reaction temperatures, PET glass transition and heating crystallization temperatures slightly decreased, melting temperature slightly increased, while degree of crystallinity was practically invariable. The DTG curves indicated that, at least, three phases remained. The OM images revealed that the morphology is constituted of a PET matrix and a PC dispersed phase. In the interfacial region we noticed the appearance of structures like bridges linking the matrix and the dispersed domains. These bridges were correlated to the PET/PC block copolymer obtained during blending in the molten state. IV increased for all polymerization temperatures, due to the occurrence of PET chain extension reactions - esterification and transesterification. The IV range for bottle grade PET was achieved.